2021
DOI: 10.2298/csis210227048t
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of degradation, security, and capacity of LSB substitution methods by a new proposed hybrid n-LSB approach

Abstract: This study proposes a new hybrid n-LSB (Least Significant Bit) substitution-based image steganography method in the spatial plane. The previously proposed n-LSB substitution method by authors of this paper is combined with the Rivest-Shamir-Adleman (RSA), RC5, and Data Encryption Standard (DES) encryption algorithms to improve the security of the steganography, which is one of the requirements of steganography, and the Lempel-Ziv-Welch (LZW), Arithmetic and Deflate lossless compression al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For the third facet i.e., reducing image degradation, it was observed that the n-Hybrid technology proposed by (Tütüncü et al, 2021) had a research gap of not considering the high degradation caused by MSBs change of the SI pixel while trying to reduce the PVD without changing secret embedded 3-LSBs. Thus, a novel d-hybrid approach which is an improvement of the n-Hybrid approach proposed by (Tütüncü et…”
Section: Motivation and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…For the third facet i.e., reducing image degradation, it was observed that the n-Hybrid technology proposed by (Tütüncü et al, 2021) had a research gap of not considering the high degradation caused by MSBs change of the SI pixel while trying to reduce the PVD without changing secret embedded 3-LSBs. Thus, a novel d-hybrid approach which is an improvement of the n-Hybrid approach proposed by (Tütüncü et…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…For the second objective, to develop a steganographic technique that is highly secured, the posited method introduced a novel M-Log chaos technique for embedding. In the end, after the embedding process, the proffered method used the d-Hybrid LSB method which is inspired from and is an amended version of the n-Hybrid LSB method proposed by (Tütüncü et al, 2021) for degradation reduction in the SI.…”
Section: Carriers Imagementioning
confidence: 99%
See 2 more Smart Citations